A medical high-strength antibacterial austenitic stainless steel and its preparation method and application

By performing low-temperature aging treatment on cold-drawn copper-containing austenitic stainless steel, the copper-rich phase is precipitated again, solving the problem of low mechanical strength of existing austenitic antibacterial stainless steel, and achieving both high strength and excellent antibacterial properties.

CN116287998BActive Publication Date: 2025-03-25FOSHAN HOSPITAL OF TCM +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310202002.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-03-03
Publication Date
2025-03-25
Estimated Expiration
2043-03-03

AI Technical Summary

Technical Problem

The existing medical austenitic antibacterial stainless steel has low mechanical strength and its antibacterial performance is reduced after cold deformation, making it difficult to meet the needs of high-strength applications.

Method used

By performing low-temperature aging treatment on cold-drawn copper-containing austenitic stainless steel, the copper-rich phase is precipitated again, and the cold-drawing defect is combined with the second phase to improve the mechanical strength and antibacterial properties of the material.

Benefits of technology

While maintaining excellent antibacterial properties, the mechanical strength of austenitic stainless steel is greatly improved, with tensile strength up to 1350-1630MPa, hardness up to 420-500HV, and sterilization rate up to 99.1-99.9%.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004109381380000061
    Figure BDA0004109381380000061
  • Figure HDA0004109381390000011
    Figure HDA0004109381390000011
  • Figure HDA0004109381390000012
    Figure HDA0004109381390000012
Patent Text Reader

Abstract

The invention belongs to the technical field of stainless steel, and specifically discloses a medical high-strength antibacterial austenitic stainless steel and a preparation method and application thereof. The chemical composition of austenitic stainless steel is C: ≤0.01, Si: 0.3-0.6, Mn: 0.8-1.2, S: ≤0.01, P: ≤0.01, Cr: 17.5-19.0, Ni: 12.5-14.5, Mo: 2.2-3.0, N: 0.1-0.2, Cu: 3.5-4.5, and the balance is Fe; the austenitic stainless steel includes cold drawing and low-temperature aging treatment. The present invention performs low-temperature aging treatment on cold-drawn copper-containing austenitic stainless steel, so that the copper-rich phase that is deformed and decomposed during the cold drawing process is precipitated again, and through the composite strengthening of cold drawing defects and the second phase, the mechanical strength is greatly improved while maintaining excellent antibacterial properties, achieving a tensile strength of 1350-1630MPa, a hardness of 420-500HV, and a sterilization rate of 99.1-99.9%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of stainless steel, and in particular to the technical field of medical stainless steel, and specifically relates to a medical high-strength antibacterial austenitic stainless steel and a preparation method and application thereof. Background Art

[0002] Medical stainless steel is a type of medical metal material with the longest application history and the widest application due to its outstanding advantages such as good mechanical properties and excellent resistance to corrosion by body fluids. Among them, medical austenitic stainless steel has been widely used in implant devices such as orthopedics and interventions because of its non-magnetic nature, high toughness and plasticity, as well as excellent corrosion resistance and biocompatibility. However, with the development of society and the improvement of people's living standards, people are paying more and more attention to the infection problems caused by implants, and the existing medical stainless steel has gradually failed to meet people's needs. Antibacterial stainless steel came into being in this context. Antibacterial stainless steel is a new type of structural / functional integrated material. It is a new type of functional material with both mechanical and antibacterial properties obtained by adding metal elements with antibacterial functions, such as copper (Cu), silver (Ag), gallium (Ga), etc., to the existing ordinary stainless steel. After a special heat treatment process, a new functional material with both mechanical properties and antibacterial properties is obtained.

[0003] At present, medical antibacterial stainless steel has attracted more and more researchers' attention. In the prior art, a kind of stainless steel for implantable medical devices with antibacterial function is prepared by adding a certain amount of rare earth and Cu elements to stainless steel and then aging treatment. Or by adding Ga elements to the austenitic stainless steel matrix and corresponding heat treatment, Fe3Ga intermediate phase can be precipitated in the austenitic matrix, thereby giving the material rapid bactericidal properties and strong antibacterial properties under high bacterial concentrations. Some also obtain a corrosion-resistant antibacterial stainless steel by adding Cu elements to the stainless steel matrix and sputtering TiO2 onto the stainless steel surface by magnetron sputtering. That is, in the existing technology about medical antibacterial stainless steel, antibacterial elements are added to stainless steel, but the strength level of the material is not paid attention to. Taking Cu-containing austenitic antibacterial stainless steel as an example, it mainly plays an antibacterial role through the copper-rich phase precipitated by aging, but compared with the common hard strengthening phases in steel such as carbonitrides, the copper-rich phase is a relatively "soft" strengthening phase in steel, and its effect on improving strength is limited. And related studies have shown that after cold deformation, this softer copper-rich phase will deform and decompose, thereby reducing its antibacterial properties.

[0004] Although austenitic antibacterial stainless steel has excellent comprehensive performance, its low mechanical strength greatly limits its application range. Especially in some environments that require high-strength performance, the application range of austenitic antibacterial stainless steel is greatly limited. At present, austenitic antibacterial stainless steel is generally strengthened by cold deformation, but after deformation strengthening, the strength of austenitic antibacterial stainless steel is still low, and after cold deformation, the antibacterial phase inside the material will deform and decompose, which also reduces its antibacterial performance to a certain extent. Therefore, it is necessary to introduce new strengthening methods to obtain high-strength austenitic antibacterial stainless steel.

[0005] Therefore, there is an urgent need to develop a medical austenitic stainless steel that can improve its mechanical properties while maintaining good antibacterial properties. Summary of the invention

[0006] The present invention aims to solve at least one of the technical problems existing in the above-mentioned prior art. To this end, the present invention proposes a medical high-strength antibacterial austenitic stainless steel and its preparation method and application, by subjecting the cold-drawn copper-containing austenitic stainless steel to low-temperature aging treatment, so that the copper-rich phase that undergoes deformation and decomposition during the cold drawing process is precipitated again, and through the cold drawing defects and the second phase composite strengthening, its mechanical strength is greatly improved while maintaining excellent antibacterial properties.

[0007] In order to solve the above technical problems, the first aspect of the present invention provides an austenitic stainless steel, whose chemical composition, by mass percentage, is C: ≤0.01%, Si: 0.3-0.6%, Mn: 0.8-1.2%, S: ≤0.01%, P: ≤0.01%, Cr: 17.5-19.0%, Ni: 12.5-14.5%, Mo: 2.2-3.0%, N: 0.1-0.2%, Cu: 3.5-4.5%, and the balance is Fe;

[0008] The process of preparing the austenitic stainless steel includes cold drawing and low temperature aging treatment.

[0009] Specifically, the present invention adds a certain amount of copper to the components of a specific austenitic stainless steel, and the copper-rich phase formed is the main precipitation phase of austenitic stainless steel with high strength and excellent antibacterial properties. For copper-containing austenitic stainless steel in a solid solution state, the precipitation nose temperature of the copper-rich phase is generally 700-800°C, and the precipitation time is about 30 minutes. At this time, the size of the precipitated copper-rich phase is generally about 20nm, and its improvement on strength is limited. The present invention adjusts the components of austenitic stainless steel and cold draws the aged copper-containing austenitic stainless steel. On the one hand, part of the copper-rich phase in the material matrix will undergo deformation and decomposition; on the other hand, a large number of deformation bands will be generated in the matrix. The defect density in these deformation bands is high, the atomic arrangement is chaotic, and it is easier for atoms to diffuse along the crystal defects. There are a large number of nucleation sites, and a large amount of deformation energy is stored in the deformation band. Therefore, after aging at a lower temperature, the copper-rich phase can be uniformly precipitated again at the deformation band. Different from the copper-rich phase directly precipitated from the solid solution, the copper-rich phase precipitated by low-temperature aging is smaller in size (<5nm), which can greatly improve the mechanical properties of the material and further give the material excellent antibacterial properties.

[0010] Preferably, the chemical composition of the austenitic stainless steel, by mass percentage, is C: ≤0.01%; Si: 0.3-0.6%; Mn: 0.8-1.2%; S: ≤0.01%; P: ≤0.01%; Cr: 17.6-19.0%; Ni: 12.8-14.5%; Mo: 2.3-2.8%; N: 0.12-0.18%; Cu: 3.5-4.5%; and the balance is Fe.

[0011] As a further improvement of the above solution, the cross-sectional deformation of the cold drawing is not less than 70%.

[0012] Specifically, the effect of this large deformation is to produce defects such as deformation bands in the material. The energy density at the deformation band is high and unstable. When low-temperature aging treatment is used, precipitation phases will be produced, and the copper-rich phase produced by low-temperature aging is smaller in size. Through nano-scale copper-rich phases (precipitation strengthening) and cold deformation strengthening (deformation strengthening), its strength and antibacterial properties can be more effectively improved. If the cold deformation is small, the deformation bands inside the material will decrease, and the corresponding volume fraction of the precipitated copper-rich phase will also decrease. The second phase strengthening and deformation strengthening are not sufficient, resulting in low strength of the material.

[0013] As a further improvement of the above scheme, the temperature of the low-temperature aging treatment is 500-600° C., and the insulation time is 30-120 minutes.

[0014] Specifically, low-temperature aging treatment at this temperature can make fine dispersed copper-rich phases precipitate evenly in the deformation zone. At the same time, the aging temperature should not be too low, and the aging time should not be too short. From a kinetic point of view, it will be unfavorable for the precipitation of the intermediate phase; while if the aging temperature is too high and the aging time is too long, the precipitated phase will be coarse, affecting the mechanical and corrosion resistance of the material. The present invention introduces a deformation zone through cold drawing, and regulates the uniform precipitation of the copper-rich phase in the deformation zone, so that the copper-containing austenitic stainless steel has high strength and excellent antibacterial properties.

[0015] A second aspect of the present invention provides a method for preparing austenitic stainless steel, the method being used to prepare the austenitic stainless steel described in the first aspect of the present invention, comprising the following steps:

[0016] (1) Smelting austenitic stainless steel raw materials, electroslag remelting, hot forging, and hot rolling to obtain hot-rolled wire rods;

[0017] (2) subjecting the hot-rolled wire rod to solution heat treatment, aging heat treatment and pickling to obtain an aged hot-rolled wire rod;

[0018] (3) The aged hot-rolled wire rod is subjected to cold drawing and low-temperature aging treatment in sequence to obtain the austenitic stainless steel.

[0019] Specifically, the commonly used heat treatment method for copper-containing antibacterial stainless steel is solid solution + aging treatment, wherein: the role of aging treatment is to precipitate copper-rich phase to ensure the antibacterial properties of the material. The present invention performs two aging treatments before and after cold drawing, especially the second low-temperature aging treatment, which can make the copper-rich phase (produced by the first aging treatment) decomposed by deformation precipitate again, which is beneficial to simultaneously improve the mechanical properties and antibacterial properties of the material.

[0020] Preferably, in step (1), the hot rolling temperature is 950-1250°C.

[0021] Preferably, in step (2), the temperature of the solution heat treatment is 1150-1250° C., and the holding time is 0.5-1 hour.

[0022] Preferably, in step (2), the aging treatment temperature is 650-750° C., and the insulation time is 5-7 hours.

[0023] Preferably, in step (3), the cross-sectional deformation amount of the cold drawing is 70-80%. Further preferably, the cross-sectional deformation amount of the cold drawing is 70-75%.

[0024] Preferably, in step (3), the temperature of the low-temperature aging treatment is 520-570° C., and the holding time is 48-108 minutes.

[0025] The third aspect of the present invention provides the use of the austenitic stainless steel described in the first aspect of the present invention in medical materials.

[0026] Preferably, the medical material comprises a medical implant material.

[0027] Compared with the prior art, the above technical solution of the present invention has at least the following technical effects or advantages:

[0028] (1) The present invention adds a certain amount of copper element to the stainless steel material, controls the chemical composition of each element, and performs cold drawing + low-temperature aging treatment on the stainless steel. Cold drawing introduces cold deformation defects (deformation bands) in the material matrix, and then uses low-temperature aging treatment to make the copper-rich phase that undergoes deformation and decomposition due to cold drawing precipitate again at the material deformation band, thereby ensuring the antibacterial property of the material. At the same time, the precipitation of the nano-scale copper-rich phase can play a role in strengthening the second phase, thereby improving the mechanical properties of the material.

[0029] (2) The austenitic stainless steel prepared by the present invention has a tensile strength of 1350-1630 MPa and a hardness of 420-500 HV; it also has excellent antibacterial properties, and the sterilization rate can reach 99.1-99.9%. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 The metallographic structure diagram of the austenitic stainless steel prepared in Example 3;

[0031] Figure 2 This is a transmission electron microscope image of the austenitic stainless steel prepared in Example 3;

[0032] Figure 3 This is a comparison chart of the mechanical properties of austenitic stainless steel before and after low-temperature aging treatment during the preparation process of Example 3. DETAILED DESCRIPTION

[0033] The present invention is described in detail below in conjunction with the examples, so that the technical personnel of the relevant technical field can understand the present invention. It is necessary to point out here that the examples are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. The non-essential improvements and adjustments made to the present invention by the skilled person in the relevant field according to the above invention content should still belong to the scope of protection of the present invention. At the same time, the raw materials mentioned below that are not described in detail are all commercially available products; the process steps or preparation methods that are not mentioned in detail are all process steps or preparation methods known to those skilled in the art.

[0034] Examples 1-6 and Comparative Examples 1-6

[0035] The chemical compositions of the austenitic stainless steels of Examples 1-6 and Comparative Examples 1-6 are shown in Table 1.

[0036] Table 1: Chemical composition of austenitic stainless steel of Examples 1-6 and Comparative Examples 1-6 (wt.%)

[0037] Material Cr Ni Mn Mo Si N Cu C S P Fe Example 1 18.2 12.8 0.9 2.3 0.6 0.14 3.8 0.004 0.001 0.004 margin Example 2 18.5 13.0 0.8 2.5 0.4 0.15 4.0 0.005 0.002 0.006 margin Example 3 19.0 13.8 1.1 2.6 0.5 0.15 4.5 0.007 0.001 0.005 margin Example 4 17.6 14.5 1.1 2.8 0.6 0.14 4.2 0.003 0.003 0.006 margin Example 5 18.5 14.0 0.9 2.4 0.3 0.18 4.0 0.008 0.002 0.006 margin Example 6 18.3 13.7 1.2 2.5 0.5 0.12 3.5 0.005 0.001 0.005 margin Comparative Example 1 19.0 13.8 1.1 2.6 0.5 0.15 4.5 0.007 0.001 0.005 margin Comparative Example 2 19.0 13.8 1.1 2.6 0.5 0.15 4.5 0.007 0.001 0.005 margin Comparative Example 3 19.0 13.8 1.1 2.6 0.5 0.15 4.5 0.007 0.001 0.005 margin Comparative Example 4 19.0 13.8 1.1 2.6 0.5 0.15 4.5 0.007 0.001 0.005 margin Comparative Example 5 19.0 13.5 0.9 2.4 0.4 0.15 3.2 0.006 0.003 0.007 margin Comparative Example 6 18.8 13.8 1.1 2.3 0.6 0.17 4.8 0.008 0.002 0.005 margin

[0038] The preparation method of the austenitic stainless steel of Examples 1-6 and Comparative Examples 1-6 comprises the following steps:

[0039] (1) According to the chemical composition range shown in Table 1, austenitic stainless steel is smelted in a vacuum induction furnace, and after electroslag remelting, hot forging and hot rolling at 1200° C. for 1 hour, a hot-rolled wire rod (bar) with a diameter of 4 mm is obtained;

[0040] (2) subjecting the hot-rolled wire rod obtained in step (1) to a solution heat treatment at 1180° C. for 1 hour, and then subjecting the hot-rolled wire rod to an aging heat treatment at 700° C. for 6 hours, and then subjecting the hot-rolled wire rod to an aging heat treatment, to obtain an aged hot-rolled wire rod;

[0041] (3) The aged hot-rolled wire rod obtained in step (2) is first cold drawn; then subjected to low-temperature aging treatment to obtain austenitic stainless steel (wire) with a diameter of 2 mm.

[0042] In the preparation methods of austenitic stainless steel of Examples 1-6 and Comparative Examples 1-6, the cross-sectional deformation and the temperature and time parameters of low-temperature aging are shown in Table 2.

[0043] Table 2: Parameters of cold drawing and low temperature aging treatment of austenitic stainless steel of Examples 1-6 and Comparative Examples 1-6

[0044] Material Cold drawn section deformation (%) Low temperature aging temperature (℃) Low temperature aging time (min) Example 1 75 520 48 Example 2 73 530 90 Example 3 72 550 40 Example 4 72 570 72 Example 5 73 520 108 Example 6 74 570 78 Comparative Example 1 72 650 40 Comparative Example 2 72 550 5 Comparative Example 3 72 440 40 Comparative Example 4 72 550 20 Comparative Example 5 72 550 40 Comparative Example 6 72 550 40

[0045] Performance Testing

[0046] 1. Microstructure

[0047] The austenitic stainless steel sample prepared in Example 3 was subjected to microstructural testing. The results are as follows: Figure 1-2 As shown by Figure 1-2 It can be seen that after cold drawing + low-temperature aging treatment, a large number of nano-scale copper-rich phases with a diameter of less than 5nm are precipitated in the deformation zone of the material substrate.

[0048] 2. Mechanical properties

[0049] According to relevant standards such as GB / T 228-2010 Tensile test of metallic materials Part 1: Room temperature test method and GB / T 4342-1991 Metal micro-Vickers hardness test method, the room temperature tensile properties and microhardness values ​​of the metals with the components shown in Table 1 (Examples 1-6 and Comparative Examples 1-6) were quantitatively tested, and the test results are shown in Table 3.

[0050] Figure 3 This is a comparison of the mechanical properties of austenitic stainless steel before and after low-temperature aging treatment in the preparation process of Example 3. The horizontal axis Engineering strain in the figure represents engineering strain; the vertical axis Engineering stress represents engineering stress. Figure 3 It can be seen that compared with single cold drawing deformation, the mechanical properties of the material after cold drawing deformation + low-temperature aging treatment have been greatly improved.

[0051] 3. Antibacterial properties

[0052] According to the relevant standards such as "JIS Z 2801-2000 "Antibacterial processed products - Antibacterial test methods and antibacterial effects", GB / T2591-2003 "Antibacterial plastics antibacterial performance test methods and antibacterial effects", the sterilization rate of the metal components (Examples 1-6 and Comparative Examples 1-6) shown in Table 1 on the common infectious pathogen - Staphylococcus aureus was quantitatively tested. The calculation formula of the sterilization rate is: Sterilization rate (%) = [(number of viable bacteria in the control sample - number of viable bacteria in the austenitic antibacterial stainless steel) / number of viable bacteria in the control sample] × 100%, the number of viable bacteria in the control sample is the number of viable bacteria after bacterial culture on the ordinary 316 austenitic stainless steel sample, and the number of viable bacteria in the austenitic antibacterial stainless steel refers to the number of viable bacteria after bacterial culture on the heat-treated austenitic antibacterial stainless steel. The test results are shown in Table 3.

[0053] Table 3: Comparison of mechanical properties and antibacterial properties of austenitic stainless steel of Examples 1-6 and Comparative Examples 1-6

[0054] From the results in Table 3, it can be seen that the austenitic stainless steels prepared in Examples 1-6 of the present invention all exhibit high-strength mechanical properties and also have excellent antibacterial properties, wherein: the tensile strength can reach 1350-1630 MPa, the hardness value can reach 420-500 HV, and the sterilization rate can reach 99.1-99.9%. That is, the excellent mechanical properties and antibacterial properties of the austenitic stainless steel prepared in the present invention are the result of the combined effect of specific chemical composition and aging treatment process.

[0055] The difference between Comparative Example 1-2 and Example 3 is that the low-temperature aging temperature is higher or the aging time is longer. As shown in Table 3, when the copper content is the same, if the aging temperature is too high or the aging time is too long, the copper-rich phase in the cold-deformed austenitic antibacterial stainless steel matrix and the grain boundary will grow abnormally. The presence of this coarse precipitate phase causes the mechanical properties of the material to decrease significantly.

[0056] The difference between Comparative Examples 3-4 and Example 3 is that the low-temperature aging temperature is lower or the aging time is shorter. As shown in Table 3, when the copper content is the same, if the aging temperature is too low or the aging time is too short, sufficient copper-rich phase cannot be precipitated in the cold-deformed copper-containing austenitic stainless steel matrix, and the performance of the material is close to that of the cold-deformed state, and it cannot have high strength and antibacterial properties.

[0057] Therefore, the low-temperature aging treatment after cold drawing in the present invention has an important influence on the antibacterial properties and mechanical properties of austenitic stainless steel.

[0058] The only difference between Comparative Example 5 and Example 3 is that the copper content is lower. As shown in Table 3, under the same low-temperature aging temperature and aging time, when the copper addition amount is too low, the supersaturation of copper in the matrix is ​​too low, resulting in the material being unable to precipitate enough copper-rich phase. Therefore, the mechanical properties and antibacterial rate of Comparative Example 5 are inferior to those of Example 3.

[0059] The only difference between Comparative Example 6 and Example 3 is that the copper content is higher. As shown in Table 3, under the same low-temperature aging temperature and aging time, when the copper addition is too high, although the material has excellent antibacterial properties, it is also easy to cause abnormal growth of the copper-rich phase and reduce its mechanical properties. In addition, too high a copper content will also seriously deteriorate the hot working properties of the material.

[0060] Therefore, only by controlling the copper content within an appropriate range and adjusting the appropriate low-temperature aging heat treatment system can the cold-deformed copper-containing austenitic stainless steel have excellent mechanical properties and antibacterial properties.

[0061] For ordinary technicians in the technical field to which the present invention belongs, several simple deductions or substitutions can be made without departing from the concept of the present invention, without having to go through creative labor. Therefore, simple improvements made to the present invention by those skilled in the art based on the disclosure of the present invention should be within the protection scope of the present invention. The above embodiments are preferred embodiments of the present invention, and all processes similar to the present invention and equivalent changes made should belong to the protection scope of the present invention.

Claims

1. An austenitic stainless steel, characterized in that: Its chemical composition, by mass percentage, is C: ≤0.01%, Si: 0.3-0.6%, Mn: 0.8-1.2%, S: ≤0.01%, P: ≤0.01%, Cr: 17.5 -19.0%, Ni: 12.5-14.5%, Mo: 2.2-3.0%, N: 0.1-0.2%, Cu: 3.5-4.5%, and the balance is Fe; The austenitic stainless steel is prepared by a preparation method comprising the following steps: (1) The austenitic stainless steel raw material is smelted, electroslag remelted, hot forged and hot rolled to obtain hot rolled wire rod; (2) subjecting the hot-rolled wire rod to solution heat treatment, aging heat treatment and pickling to obtain aged hot-rolled wire rod; the aging heat treatment temperature is 650-750° C., and the holding time is 5-7 hours; (3) The aged hot-rolled wire rod is subjected to cold drawing and low-temperature aging treatment in sequence to obtain the austenitic stainless steel; the cross-sectional deformation of the cold drawing is 70-80%; the temperature of the low-temperature aging treatment is 520-570° C., and the holding time is 48-108 minutes.

2. The austenitic stainless steel according to claim 1, characterized in that: In step (1), the hot rolling temperature is 950-1250°C.

3. The austenitic stainless steel according to claim 1, characterized in that: In step (2), the temperature of the solution heat treatment is 1150-1250° C., and the holding time is 0.5-1 hour.

4. Use of the austenitic stainless steel according to any one of claims 1 to 3 in medical materials.

Citation Information

Patent Citations

  • Anti-infection medical stainless steel

    CN102234739A

  • Preparation method of ultrahigh-strength high-corrosion-resistance high-nitrogen austenitic stainless steel

    CN114934240A